Behavioral Constraints on Pricing: Experimental Evidence on Price Discrimination and Customer Antagonism - Andreas Leibbrandt (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this study, we investigate behavioral constraints on pricing by using a novel laboratory experiment in which actual consumption goods are traded. We test different models and provide several insights into pricing and reactions to price discrimination. First, we identify the extent to which sellers voluntarily and strategically avoid price discrimination. Second, we find that sellers strategically overprice low value customers to avoid antagonizing high value customers. Third, we observe that customers are not generally antagonized by price discrimination: while they are less likely to buy if they are charged a higher price than another customer even if they are underpriced, they are more likely to buy if they are charged a lower price even if they are overpriced. These findings are consistent with a reference point model, which assumes that prices for other customers constitute reference points. Finally, we show that our findings hold regardless of whether sellers are monopolists or compete against other sellers. The observed behavioral patterns suggest a novel explanation for sticky prices and impulse purchase behavior.
Keywords: L11; C99; 330; price discrimination; customer antagonism; fairness; reference points